Estimates of magnetotail reconnection rate based on IMAGE FUV and EISCAT measurements - Østgaard, N.; Moen, J.; Mende, S. B.; Frey, H. U.; Immel, T. J.; Gallop, P.; Oksavik, K.; Fujimoto, M. (HAL CCSD, 2005)
International audience Dayside merging between the interplanetary and terrestrial magnetic fields couples the solar wind electric field to the Earth's magnetosphere, increases the magnetospheric convection and results in efficient transport of solar wind energy into the magnetosphere. Subsequent reconnection of the lobe magnetic field in the magnetotail transports energy into the closed magnetic field region. Combining global imaging and ground-based radar measurements, we estimate the reconnection rate in the magnetotail during two days of an EISCAT campaign in November-December 2000. Global images from the IMAGE FUV system guide us to identify ionospheric signatures of the open-closed field line boundary observed by the two EISCAT radars in Tromsø (VHF) and on Svalbard (ESR). Continuous radar and optical monitoring of the open-closed field line boundary is used to determine the location, orientation and velocity of the open-closed boundary and the ion flow velocity perpendicular to this boundary. The magnetotail reconnection electric field is found to be a bursty process that oscillates between 0mV/m and 1mV/m with ~10-15min periods. These ULF oscillations are mainly due to the motion of the open-closed boundary. In situ measurements earthward of the reconnection site in the magnetotail by Geotail show similar oscillations in the duskward electric field. We also find that bursts of increased magnetotail reconnection do not necessarily have any associated auroral signatures. Finally, we find that the reconnection rate correlates poorly with the solar wind electric field. This indicates that the magnetotail reconnection is not directly driven, but is an internal magnetospheric process. Estimates of a coupling efficiency between the solar wind electric field and magnetotail reconnection only seem to be relevant as averages over long time intervals. The oscillation mode at 1mHz corresponds to the internal cavity mode with additional lower frequencies, 0.5 and 0.8mHz, that might be modulated by solar wind ...